The Mental and Physical Burden of Caregiving - Evidence from Administrative Data - Magdalena A. Stroka (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
This study evaluates the mental and physical strain experienced by informal caregivers. Econometric problems due to individuals selecting themselves into informal care provision are tackled by using informative and detailed data from the largest sickness fund in Germany and applying propensity score matching techniques. The findings suggest that carers take more psychoactive drugs as well as analgesics and gastrointestinal agents. Thus, informal caregiving appears to be a burdensome task with implications for both mental and physical health. – – Die vorliegende Studie verfolgt das Ziel der Aufdeckung von Opportunitätskosten die mit der Erbringung der informellen Pflege Angehöriger einhergehen und sich in der Verschlechterung des Gesundheitszustandes der pflegenden Personen äußern. Hierzu werden die Routinedaten Deutschlands größter Krankenkasse verwendet. Unter Rückgriff auf die Methode des Propensity Score Matchings liefert die Untersuchung Evidenz für eine höhere Einnahme von Psychopharmaka sowie Schmerz- und Verdauungsmitteln durch informelle Pfleger im Vergleich zu Personen ohne Pflegeverpflichtungen. Es scheint also, als dass informelle Pflege sowohl mit mentaler als auch physischer Gesundheitsbelastung einhergeht.
Keywords: I10; 330; informal care; burden; drugs; propensity score matching